2019
DOI: 10.2478/prilozi-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome (PRES) in Children Undergoing Allogeneic Stem Cell Transplantation

Abstract: Posterior reversible encephalopathy syndrome (PRES) is one of the most serious complication after allogeneic stem cell transplantation in paediatric setting. It is most commonly reported as adverse event of immunosuppressive strategies during transplantation. We present a case of a 7 years old girl with myelodysplastic syndrome (MDS) treated with allogeneic stem cell transplantation (ASCT) at our department. Diagnosis of PRES was confirmed by imaging techniques during the first month after transplant and it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
3
0
0
Order By: Relevance
“…The literature stated that the most common finding for PRES is a high signal on T2WI and FLAIR sequences. This supported the current study results where CT and T1WI MRI findings of our PRES patients were inconclusive, and the main distinctive features were the high T2 and FLAIR signals [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The literature stated that the most common finding for PRES is a high signal on T2WI and FLAIR sequences. This supported the current study results where CT and T1WI MRI findings of our PRES patients were inconclusive, and the main distinctive features were the high T2 and FLAIR signals [13].…”
Section: Discussionsupporting
confidence: 92%
“…During the follow-up, PRES was much more common at the < 100 day-post-HSCT period, during which 70.6% of PRES episodes occurred. These results are rather comparable to the findings of Veljanovska et al [13] and Siegal et al [15], which revealed that 86% of PRES episodes occurred during the first 100 days post-transplant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation